Financial Literacy: Empowering Women for Better Financial Management - Ela Elliyana; Yuliani Yuliani; Ambo Paerah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
Previous research has shown that women tend to have lower levels of financial literacy and participation in economic activities than men. The research aims to determine ways for women to empower themselves by improving their financial literacy. The research design, a literature study, is based on a review of articles using appropriate keywords, aiming to identify and objectively evaluate relevant research on the topic of financial literacy in women, the determinants, and applicable criteria approaches to enhancing financial literacy, using a transparent process to minimize research bias. Although this systematic literature review is not comprehensive, the research has been complex. The systematic review involves thorough literature searching, explicit criteria for the inclusion and exclusion of studies, and a reliable assessment of the quality of the cited research. The research findings indicate several appropriate methods, including understanding the basics of financial literacy, taking control of personal finances, using technology, making smart investments, and seeking professional assistance in managing and consulting on finances